A Transmetalation Reaction Enables the Synthesis of [18F]5-Fluorouracil from [18F]Fluoride for Human PET Imaging - Hoover, Andrew J (Organometallics, 2016)
Translation of new 18F-fluorination reactions to produce radiotracers for human positron emission tomography (PET) imaging is rare because the chemistry must have useful scope and the process for 18F-labeled tracer production must be robust and simple to execute. The application of transition metal mediators has enabled impactful 18F-fluorination methods, but to date none of these reactions have been applied to produce a human-injectable PET tracer. In this article we present chemistry and process innovations that culminate in the first production from [18F]fluoride of human doses of [18F]5-fluorouracil, a PET tracer for cancer imaging in humans. The first preparation of nickel σ-aryl complexes by transmetalation from arylboronic acids or esters was developed and enabled the synthesis of the [18F]5-fluorouracil precursor. Routine production of >10 mCi doses of [18F]5-fluorouracil was accomplished with a new instrument for azeotrope-free [18F]fluoride concentration in a process that leverages the tolerance of water in nickel-mediated 18F-fluorination